Botulism with Unusual Rapid Progression to Complete Paralysis in a Child - Hui-Ju Tsai; Wen-Chen Liang; Chien-Hua Wang; Po-Ching Chou; Jong-Hau Hsu; Chia-Tsuan Huang; Yuh-Jyh Jong (Elsevier, 2015)
Botulism is a severe neuroparalytic illness which is difficult to diagnose accurately, especially in children. We report a child with type A botulism intoxication, with very rapid progression to coma-like consciousness and respiratory failure. Careful physical examinations led to the suspicion of botulism, and electrophysiologic examinations, including electroencephalogram and repetitive nerve stimulation tests, further supported the diagnosis. Hospitalization due to botulism had a great emotional impact on the patient and psychological support was crucial.